Wildly Growing Asparagus (Asparagus officinalis L.) Hosts Pathogenic Fusarium Species and Accumulates Their Mycotoxins - Stępień, Łukasz (Microb Ecol, 2015)
Asparagus officinalis L. is an important crop in many European countries, likely infected by a number of Fusarium species. Most of them produce mycotoxins in plant tissues, thus affecting the physiology of the host plant. However, there is lack of information on Fusarium communities in wild asparagus, where they would definitely have considerable environmental significance. Therefore, the main scientific aim of this study was to identify the Fusarium species and quantify their typical mycotoxins present in wild asparagus plants collected at four time points of the season. Forty-four Fusarium strains of eight species—Fusarium acuminatum, Fusarium avenaceum, Fusarium culmorum, Fusarium equiseti, Fusarium oxysporum, Fusarium proliferatum, Fusarium sporotrichioides, and Fusarium tricinctum—were isolated from nine wild asparagus plants in 2013 season. It is the first report of F. sporotrichioides isolated from this particular host. Fumonisin B(1) was the most abundant mycotoxin, and the highest concentrations of fumonisins B(1)–B(3) and beauvericin were found in the spears collected in May. Moniliformin and enniatins were quantified at lower concentrations. Mycotoxins synthesized by individual strains obtained from infected asparagus tissues were assessed using in vitro cultures on sterile rice grain. Most of the F. sporotrichioides strains synthesized HT-2 toxin and F. equiseti strains were found to be effective zearalenone producers.